Técnicas, procedimentos e mandato policial: um estudo sobre a atuação da Polícia Militar de Minas Gerais em Belo Horizonte - Prado, Sara Carla Faria (2019)
The present research sought to present the work carried out by the military police of Minas Gerais, in the city of Belo Horizonte. The objective was to understand, from the view of the police themselves, how the dimensions related to the daily work impact their actions in the streets of the capital of Minas Gerais. In order to do so, it was sought to demonstrate, through a vast theoretical framework, dimensions such as culture, mandate, discretion and training. Next, organizational documents were analyzed, mainly related to the technical training offered by the institution itself. Finally, an analysis of the interviews conducted with the military of Belo Horizonte.